PENERAPAN SISTEM E-PERFORMANCE DAN PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) TERHADAP KINERJA ASN : WORK MOTIVATION SEBAGAI VARIABEL INTERVENING - MAULIDZA NUR FAUZI (STIE Mahardhika, 2023)
This study discusses the Effectiveness of Implementing the E-Performance System and Providing Additional Employee Income (TPP) on the Performance of the State Civil Apparatus (ASN) through Work Motivation as an Intervening Variabael. The type of research used is quantitative research. The population in this study were all State Civil Apparatus (ASN) at the Lamongan Regency Health Office. Sampling in this study is using the total sampling technique, which means that the entire population is sampled, totaling 87 people. The data analysis method used in this study is path analysis. The results showed that: the E-Performance variable has a positive and significant effect on ASN performance, but the E-Performance variable has no effect on the work motivation variable. Then the Employee Income Supplement (TPP) variable has no effect on the ASN performance variable, but the Employee Income Supplement (TPP) variable has a positive and significant effect on work motivation. Then for the work motivation variable has a positive and significant effect on ASN performance. The E-Performance variable has no effect on ASN performance through work motivation as an intervening variable, while the Employee Income Supplement (TPP) variable has an indirect effect on ASN performance through work motivation as an intervening variable.